2015
DOI: 10.1152/ajpendo.00267.2015
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol blocks the RhoA/ROCK1 pathway in human aortic smooth muscle cells

Abstract: -2-Methoxyestradiol (2-ME), a metabolite of estradiol with little affinity for estrogen receptors, inhibits proliferation of vascular smooth muscle cells; however, the molecular mechanisms underlying this effect are incompletely understood. Our previous work shows that 2-ME inhibits initiation (blocks phosphorylation of ERK and Akt) and progression (reduces cyclin expression and increases expression of cyclin inhibitors) of the mitogenic pathway and interferes with mitosis (disrupts tubulin organization). Beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A recent study showed that 2-ME inhibits serum-induced vascular smooth muscle cell (VSMC) migration and proliferation by blocking the RhoA/ROCK1 pathway both by inhibiting the activation of RhoA and by reducing the expression of ROCK1. 43 Whether 2-ME mediates the effect of estradiol to protect against Ang II-induced hypertension, cardiac fibrosis, renal dysfunction, and end-organ damage in OVX and Cyp1b1 − / − female mice and in Cyp1b1 +/+ male mice by inhibiting the RhoA/ROCK11 pathway remains to be determined. Oxidative stress is known to contribute to Ang II-induced hypertension and its pathogenesis in various models of hypertension including in Cyp1b1 − / − and OVX Cyp1b1 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that 2-ME inhibits serum-induced vascular smooth muscle cell (VSMC) migration and proliferation by blocking the RhoA/ROCK1 pathway both by inhibiting the activation of RhoA and by reducing the expression of ROCK1. 43 Whether 2-ME mediates the effect of estradiol to protect against Ang II-induced hypertension, cardiac fibrosis, renal dysfunction, and end-organ damage in OVX and Cyp1b1 − / − female mice and in Cyp1b1 +/+ male mice by inhibiting the RhoA/ROCK11 pathway remains to be determined. Oxidative stress is known to contribute to Ang II-induced hypertension and its pathogenesis in various models of hypertension including in Cyp1b1 − / − and OVX Cyp1b1 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that 2ME2 binding to GPR30 mediated transactivation of EGFR and activation of ERK1/2 in RASMCs. 2ME2 is an antiproliferative agent that has been shown to lead to cell cycle arrest in human aortic smooth muscle cells through the RhoA/ROCK1 pathway (59). In our study 2ME2 transactivates EGFR that phosphorylates the MAP-kinase/ERK1/2 pathway, which does not show increased cell proliferation, although EGFR/MAPK/ ERK is an established growth promoting signaling pathway.…”
Section: C563 Mmp9 and Egfr In 2me2-mediated At1r Downregulationmentioning
confidence: 50%
“…Our previous studies show that 17bestradiol, the major ovarian estrogen, is a potent inhibitor of CF, GMC, and vascular smooth muscle cell proliferation induced by serum. Moreover, these effects of 17b-estradiol are mediated by the conversion of 17b-estradiol to 2ME (Dubey et al, 1998(Dubey et al, , 2000(Dubey et al, , 2003a(Dubey et al, ,b, 2004(Dubey et al, , 2007Xiao et al, 2001;Zacharia et al, 2001Zacharia et al, , 2002Zacharia et al, , 2003Barchiesi et al, 2002Barchiesi et al, , 2006Barchiesi et al, , 2010Dubey and Jackson, 2009;Rigassi et al, 2015), a major nonestrogenic metabolite of 17b-estradiol. Therefore, it is conceivable that because of endogenous 2ME, premenopausal women are resistant to the growthpromoting effects of DPP4 inhibition, NPY 1-36 , SDF-1a, or their combination.…”
Section: Discussionmentioning
confidence: 99%